WORD OF MOUTH SEBAGAI KOMUNIKASI PEMASARAN PRODUK HANDMADE ANAK BERKEBUTUHAN KHUSUS - Oktaviani, Femi; Asydah, Siti Sonia (Universitas Swadaya Gunung Jati, 2023)
Marketing communication activities are not an easy thing to do to market products so that they can be accepted and consumed by consumers. Marketing communication for children with special needs needs more attention to ensure that others can receive the message properly. This study focuses on marketing communication activities through word of mouth by children with special needs in marketing Handmade products such as bin bags and bags. It is rare to find children with limitations who can produce and market their products to potential customers. The research objective is to find out the types, steps and dimensions of word of mouth carried out by children with special needs in marketing handmade products. This research is qualitative research with a case study approach. Data was obtained through observation and interviews and supported by researcher documentation. The results showed that organic word of mouth as a type of word of mouth in marketing communication of handmade products for children with special needs, occurs naturally from consumers of handcrafted products to others. There are five steps in word of mouth; creating good service, identifying details about the uniqueness of handmade products, understanding product segmentation, building relationships with consumers and utilizing social media. Furthermore, the dimensions of word of mouth used; talkers, topics and taking part in an effort to increase consumer confidence in handmade products produced by children with special needs. Keywords: Word of mouth, Children with special needs, Handmade